Numerical Study of Heat Sink Models Mosquito Hotend on FDM 3D Printer to Determine Heat Transfer Characteristics - Rafi Fadhlurrohman; Bambang Arip Dwiyantoro (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2024)
Fused Deposition Modelling 3D printing technology is generally used to print polymer-based materials in the form of filaments. The FDM process begins with the filament entering the liquifier area through the throat using a filament feed mechanism. During this process, clogging often occurs in hotend components because the filament melts before reaching heat block. The clogging phenomenon will result in the filament unable to extrude properly, so that the results are not optimal. In this research, numerical study will be carried out to review the temperature distribution of the Mosquito hotend, as well as the effect of variations in air flow velocity at speeds of 0 m/s, 0.25 m/s, 0.5 m/s, 0.75 m/s, and 1 m/s. Based on the results of the CFD simulation, it was observed that the temperature at the Mosquito hotend is spread asymmetrically. On the heat sink component, the part facing the inlet of the airflow and the farthest point from the heater, has a lower temperature than the opposite side. This causes an asymmetrical temperature distribution during the heat break, so that the filament melting process does not occur evenly, which will result in clogging. In addition, airflow with a faster velocity will provide a better cooling system quality. This happens because the convection coefficient increases with the increase in air velocity, thereby increasing the amount of heat to be dissipated.